Effect of atorvastatin gel in non-surgical treatment of peri-implant mucositis: A randomized controlled clinical trial - Azin Khorramdel; Katayoun Mogharrab Alile; Yousef Kananizadeh; Seyed Amin Mousavi; Fatima Molavi (Journal of Advanced Periodontology and Implant Dentistry)
Background. Peri-implant diseases, such as peri-implant mucositis and peri-implantitis, are inflammatory conditions caused by biofilms that can lead to the loss of surrounding soft tissues and bone. The most effective treatment involves non-surgical mechanical debridement to remove plaque, but other treatment modalities have shown limited success. This study investigated the anti-inflammatory and immunomodulatory effects of atorvastatin (ATV) gel as an additional treatment for peri-implant mucositis. Methods. In this double-masked, randomized clinical trial, 49 patients with peri-implant mucositis were randomly divided into two treatment groups: mechanical debridement (MD)+placebo or MD+ATV gel. At baseline, 1 month, and 3 months after the intervention, periodontal parameters, including probing depth (PD), bleeding on probing (BOP), clinical attachment level (CAL), and pain on probing (POP), were measured. Data were analyzed using independent t-test and paired t-test. Results. Statistically significant improvements in CAL and POP were observed from baseline to each time point throughout the study period (P≤0.001). PD and BOP were statistically significant 1 month and 3 months after the intervention, respectively (P<0.05). Conclusion. The clinical parameters associated with peri-implant mucosal inflammation further improved when ATV gel was used with MD.